iSLAM TARiHiNDE UYGULANAN DEVLET BAŞKANLIGI . SEÇiM ŞEKiLLERi VE ŞER'i TAHLiLi - Köksal, İsmail (Fırat University, 2006)
Except for Sheas there are six kind of election for precidiency in Islami c History. The fırst of them is election of president by whole muslims. The second is election of president by a special coımcil. The third is election of president by principality. Theforthis determination ofpresident by inberitance. The fıfth is the way of being presidient from a special family. The sixth is the way of being president by force. But, the presidiency in Sheas is special for Alıl-i Bayt.
Keywords: Religious Studies; Din Araştırmaları